The status of temporomandibular and cervical spine education in credentialed orthopedic manual physical therapy fellowship programs: a comparison of didactic and clinical education exposure. (23rd February 2015) - Shaffer, Stephen M.; Brismée, Jean-Michel; Courtney, Carol A.; Sizer, Phillip S.
Abstract : Objective: The purpose of this investigation was to establish a baseline of physical therapist education on temporomandibular disorders (TMD)-related topics during credentialed orthopedic manual physical therapy fellowship training and compare it to cervical spine disorders education. Method: An online survey was distributed electronically to each fellowship program credentialed by the American Physical Therapy Association (APTA) and recognized by the Academy of Orthopedic Manual Physical Therapists (AAOMPT). Data were analyzed to compare overall exposure to TMD educational content, including a direct comparison of TMD and cervical spine disorders education. Results: The response rate was 79%. Thirteen programs (87%) reported providing both didactic and clinical training on both TMD and cervical spine disorders. Didactic education for cervical spine disorders ranged from 16–20 hours to over 25 hours, whereas TMD hours ranged from 0 to 6–10 hours. Clinical education for cervical spine disorders ranged from 11–15 hours to over 25 hours, whereas TMD hours ranged from 0 to 6–10 hours. The number of hours of exposure during didactic training and the number of patients exposed to during clinical training were significantly different when comparing TMD to cervical spine disorders exposure ( P <0·0001). Discussion: The data indicate a lack of uniformity between credentialed fellowship programs in orthopedic manual physical therapy with respect to the extent to which programs expose trainees to evaluation and management of TMD. There is consistency in that all programs provided more training on cervical spine disorders than TMD. Despite a high level of clinical specialization, fellows-in-training receive minimal TMD education.